2019
DOI: 10.3390/ma12142269
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Saturated Tea Waste and Perlite Particles on Early Age Hydration of High-Strength Cement Mortars

Abstract: The main purpose of this work is to study the effect of saturated black tea waste and perlite on controlling the rapid heat of hydration in high-strength cement mortars at early ages. Tea waste and perlite were investigated as internal curing agents in different mixes. Mortar specimens with two different sizes of tea waste and perlite particles with 1 and 3% by volume of cement were added in different mixes to find their effect on early age hydration. The rising interior temperature, setting times, and strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Liu et al [46] reported a reduction in strength of cenosphere-containing mortars at the early ages compared to control mixes. Jakhrani et al [26] used tea waste and perlite particles in high-strength mortars to control early age hydration and heat release rates. They found a reduction in compressive strengths as compared to the control mix after curing for 3 days.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Liu et al [46] reported a reduction in strength of cenosphere-containing mortars at the early ages compared to control mixes. Jakhrani et al [26] used tea waste and perlite particles in high-strength mortars to control early age hydration and heat release rates. They found a reduction in compressive strengths as compared to the control mix after curing for 3 days.…”
Section: Resultsmentioning
confidence: 99%
“…From the evaluation of compressive strength test results, it is established that the addition of tea waste particles reduces the compressive strength of specimens, however, a gain in strength increases with the passage of time. More gain is found in the specimens that contained tea waste and perlite particles with the addition of silica fume [26].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations